One-Step Electrochemical Synthesis of Molybdenum-Disulfide-Based Materials for Enhanced Supercapacitor Performance - Hacinecipoglu, Ayse V.; Demir, Ozge; Gencten, Metin; Sahin, Yucel (ELECTROCHEMICAL SOC INC, 2024)
Molybdenum disulfide (MoS2)-based two-dimensional materials were produced in one-step at room temperature using cyclic voltammetry technique. These materials were then used as electrode materials in supercapacitors. Concentration of supporting electrolyte, precursor, and cycle number parameters, which were the factors affecting the success of the synthesis, were optimized as 0.5 M, 0.15 M,and 10 cycles, respectively. The produced MoS2-coated electrodes were characterized using spectroscopic and microscopic methods. The chemical characterizations of the produced materials were examined by X-ray photoelectron spectroscopy, X-ray diffraction diffractometry, and scanning electron microscopy-energy-dispersive X-ray analysis. Surface morphologies of the composite materials were investigated using scanning electron microscopy. Finally, the produced MoS2-based materials were used as electrode materials in supercapacitors. The produced supercapacitors were characterized using cyclic voltammetry and electrochemical impedance spectroscopy methods, and the changes in the capacitive behavior of these systems over cycles were investigated using the cyclic charge-discharge technique. The highest areal capacitance value was determined as 251 mF.cm-2 at 0.2 mA.cm-2 charge-discharge current rates in 1.0 M H2SO4 by using of MoS-AD1 as the electrode material. Capacitance retention of this electrode was over 100% after 4000 cycles. MoS2 was synthesized in one-step by cyclic voltammetry.2H-MoS2 phase was selectively electrodeposited on PGE surface by electrochemical method.251 mF.cm-2 areal capacitance was determined at 0.2 mA.cm-2 charge-discharge current rates.Capacitance retention of this electrode was over 100% after 4000 cycles.
Keywords: electrochemical impedance spectroscopy; cyclic voltammetry; 2-dimensional material; molybdenum disulfide; supercapacitors; HYDROTHERMAL SYNTHESIS; THIN-FILM; MOS2; HYBRID; ELECTRODE; NANOCOMPOSITE; COMPOSITES; SIMULATION; ANODE; Materials Science; Physics